Multi-scaling of the Dense Plasma Focus - Saw, S. H.; Lee, S. (IOP Publishing Ltd, 2015)
The dense plasma focus is a copious source of multi-radiations with many potential new applications of special interest such as in advanced SXR lithography, materials synthesizing and testing, medical isotopes and imaging. This paper reviews the series of numerical experiments conducted using the Lee model code to obtain the scaling laws of the multi-radiations.